Konsep Menjaga Lingkungan dalam Prespektif Lintas Agama di Indonesia - Shokhibul Mighfar; Muhammad Munadi; Uwais Chesoh (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2025)
The environmental crisis has become a serious threat to the survival of human life and ecosystems in the world.  This study aims to explore the concept of interfaith perspective teachings in Indonesia in shaping the attitude of religious people towards the environment and the differences and similarities of interfaith concepts in protecting the environment. Library Research method is used in this research. The results showed that there are several interfaith concepts in Indonesia in protecting the environment.  Islam is based on the concept of tawhid where humans are responsible for protecting the environment as a form of worship to Allah SWT. Catholic and Protestant Christian views of the environment are associated with the concept of Stewardship. The Hindu view of the environment is based on the concept of organic unity, which emphasizes the interconnectedness of all living things, as well as the principles of Ahimsa and Karma. Buddhism also views the environment based on the concept of mutual dependence. Meanwhile, Confucianism is based on the concepts of Tao and Wu Wei. Although there are differences across religions in the concept of protecting the environment. Each religion emphasizes the urgency of protecting the environment, treating living beings well, understanding the interconnectedness of beings, maintaining the balance of nature, and saving money.